A Implementation of the parent involvement program at BKB Kemas Lestari - Saputra, Salwa Tsabitha; Rahma, Adelia; Annastasia, Dhea; Pratiwi, Dini Putri; Nurunnisa, Fadila; Alpita, Nur; Pratiwi, Rika Luthfia; Kiromiyah, Zulfatul (International Conference on Education in Primary and Early Childhood, Marine, Computer Information, and Logistics, 2025)
Parental involvement in early childhood education is essential to support their optimal development. Bina Keluarga Balita (BKB) acts as a forum that encourages parental participation through various educational programs and collaborative activities that involve parents in the child’s learning process. This study aims to analyze the implementation of parent involvement programs at Bina Keluarga Balita (BKB) Kemas Lestari. The research used a qualitative approach with the descriptive methode. Data was collected through observation, in-depth interviews, and documentation involving the school principal and teachers. The results showed that the parent involvement program has had a positive impact on increasing parents’ knowledge about parenting and the importance of early stimulation. However, the implementation of the program faces several challenges, such as limited human resources, limited time, and varying levels of parental participation.